2018
DOI: 10.1002/aenm.201800022
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processable Conjugated Polymers as Anode Interfacial Layer Materials for Organic Solar Cells

Abstract: With appropriate charge transport layers, one can rationally engineer the driving force, which generally refers to the built-in electric field in devices, so that electrons and holes can be effectively extracted to their respective electrodes, and thereby maximize the efficiency of OSCs. [4] There are two main types of charge transport materials that are commonly used in OSCs: anode interfacial layer (AIL) materials for hole collection and electron transport layer (ETL) materials for electron collection. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 185 publications
(227 reference statements)
1
77
0
Order By: Relevance
“…Among them, some active layers have already reached near 100% internal quantum efficiencies for the conversion of absorbed photons to photogenerated carriers . In such devices, the properties of interfacial materials become more influential, even deterministic to the overall performances of OSCs and PVSCs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, some active layers have already reached near 100% internal quantum efficiencies for the conversion of absorbed photons to photogenerated carriers . In such devices, the properties of interfacial materials become more influential, even deterministic to the overall performances of OSCs and PVSCs …”
Section: Introductionmentioning
confidence: 99%
“…It is because n-doping requires molecular dopant possessing high-lying HOMO (or In such devices, the properties of interfacial materials become more influential, even deterministic to the overall performances of OSCs and PVSCs. [9,[29][30][31][32][33][34][35][36] Although some classical metal oxides, such as zinc oxide (ZnO), titanium oxide (TiO x ), and tin oxide (SnO x ), are widely used in OSCs and PVSCs as interfacial materials, [37][38][39][40][41][42][43] they, however, typically require harsh preparation for improving crystallinities, and therefore charge mobilities, which have difficulty being compatible with low-temperature processed devices, for example, flexible optoelectronics with plastic substrates. Besides, metal oxides possess intrinsic lattice defects, which could trap free charges to induce carrier recombination loss of devices.…”
Section: Introductionmentioning
confidence: 99%
“…The advances in photoactive material synthesis and engineering led to a breakthrough in increasing OSC power conversion efficiency (PCE), and recently PCEs exceeding 15% have been reported . Along with the enhancement of PCEs, various efforts, such as the modification of photoactive materials, introduction of additives, and interface engineering by improving the properties of the interfacial layer (IL), have been devoted for improving the operational stability of the completed solar cells, as well as further enhancing device efficiency …”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Along with the enhancement of PCEs, various efforts, such as the modification of photoactive materials, introduction of additives, and interface engineering by improving the properties of the interfacial layer (IL), have been devoted for improving the operational stability of the completed solar cells, as well as further enhancing device efficiency. [10][11][12] The demand for a highly efficient and stable IL, acting as an electrode modifier and charge-transporting layer, led to the development of various types of ILs including conducting polymers, self-assembled monolayers, conjugated polyelectrolytes, and metal oxides. [13][14][15][16][17][18][19] To date, a large number of studies for cathode ILs have been undertaken, whereas relatively few studies were reported for anode ILs, which simultaneously serve as good efficiency enhancers and stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Since PEDOT:PSS was invented by Bayer AG company in 1994, it has been widely applied as conductive film in organic optoelectronic devices, electrochemical energy conversion and storage devices, biosensors, thermoelectric devices, etc. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The conductivities of the most widely used Clevios P VP AI 4083 and PH1000 are between 10 À 3 -10 À 4 and 0.2-1 S⋅cm À 1 , respectively. However, owing to the high difficulty in the design and synthesis of polymeric dopants, only a limited amount of PEDOT:PSS alternatives have been reported.…”
Section: Introductionmentioning
confidence: 99%